Assessing traffic management measures in the city roads of Kuala Lumpur - Kadar Hamsa, Abdul Azeez (IIUM Press, 2011)
Traffic congestion is a normal phenomenon in many cities of the world. Nevertheless, the degree of traffic congestion differs between cities mainly due to travel demand, supply of road infrastructure, public transport facilities, parking availability etc. The city roads of Kuala Lumpur are also subjected to traffic congestion during different times of the day especially in the morning and evening hours. This is being associated mainly with work trips. High car ownership level, one of the highest in Asian cities, among others is one of the principal reasons for increasing traffic congestion in KL city roads. The local authority had introduced few traffic management measures such as one-way street system, exclusive/priority bus lanes, tidal flow operation system and prohibited right-turn at selected intersections to help alleviate traffic congestion within core urban areas especially during peak hours. An observational approach was employed to study the operational conditions of exclusive bus lanes in KL city roads. This chapter highlights the significance and literature related to exclusive bus lanes, its operational attributes, and the extent to which it would help alleviate traffic congestion in the city roads of Kuala Lumpur.